Analysis of School Library Utilization in Developing a Literacy Culture for Elementary School Students at SDN Bendelan 1 - Khotimah, Husnul; Riady, Yasir; Evriza, Eka (LADU: Journal of Languages and Education, 2024)
Background: The cultural climate of literacy for elementary school students is intricately linked to the crucial role played by school libraries. Recognizing the significance of this connection, the research delves into understanding how school libraries contribute to the development of a robust literacy culture among elementary school students. Purpose: The primary aim of this research is to analyze the role of school libraries in fostering a literacy culture among elementary school students. Employing a descriptive qualitative research method, the study seeks to investigate the extent of library utilization, focusing on aspects such as book variety, literacy programs, and strategies designed to captivate students' interest in reading. Additionally, the research aims to explore collaborative efforts between librarians and teachers in enhancing students' literacy culture. Design and methods: The research employs a descriptive qualitative research method, utilizing interviews, observation, and documentation to collect data from school principals, teachers, and students. The data analysis focuses on evaluating the extent of library usage, the adequacy of book collections, and the effectiveness of literacy programs and strategies. The design also incorporates an examination of collaborative initiatives between librarians and teachers to attract students' interest in developing their literacy culture. Results: The findings of the research highlight the current state of the library collection at SDN Bendelan 1, indicating its adequacy but emphasizing the need for improvement in alignment with the Merdeka Curriculum. The results underscore the importance of ongoing development to ensure the relevance of library materials to the curriculum, ultimately meeting the evolving learning needs of elementary school students. This research provides valuable insights for educators, librarians, and policymakers to strategically enhance literacy initiatives in elementary schools through focused library collection development.